2007
DOI: 10.3324/haematol.10774
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor repertoire usage after allografting differs between CD4+CD25+ regulatory T cells and their CD4+CD25 counterpart

Abstract: Background and ObjectivesAfter allogeneic haematopoietic stem cell transplantation (SCT) the whole T-cell receptor (TCR) repertoire shows a markedly skewed pattern for 2-3 years. A small fraction of CD4 + T cells is represented by CD25 + regulatory lymphocytes (Treg), which play a crucial role in modulating peripheral tolerance. To investigate their ability to react to the massive antigenic stimulation generated in an allogeneic host, which could significantly affect their pattern of reconstitution, we analyze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 48 publications
1
3
0
Order By: Relevance
“…A significant correlation was demonstrated between increased number of CD4 + Treg and several markers of disease aggressiveness, such as bone marrow blast infiltration >5%, high International Prognostic Scoring System (IPSS) score and disease progression, while none of these correlations was significant for CD8 + Treg (25). This study also confirmed that Treg display a polyclonal CDR3 profile, as already observed in the postallograft setting (26). In addition, most Treg were shown to belong to the naive subset, especially in high‐risk patients (25).…”
Section: The Role Of Specific Cell Types In Mdssupporting
confidence: 89%
“…A significant correlation was demonstrated between increased number of CD4 + Treg and several markers of disease aggressiveness, such as bone marrow blast infiltration >5%, high International Prognostic Scoring System (IPSS) score and disease progression, while none of these correlations was significant for CD8 + Treg (25). This study also confirmed that Treg display a polyclonal CDR3 profile, as already observed in the postallograft setting (26). In addition, most Treg were shown to belong to the naive subset, especially in high‐risk patients (25).…”
Section: The Role Of Specific Cell Types In Mdssupporting
confidence: 89%
“…Furthermore, these data rule out the possibility that a change in the repertoire of the conventional T cell pool of the recipient as a result of the homeostatic expansion (36) is the main factor responsible for a reduction or deletion in the number of HYspecific T cell precursors. As a confirmation of this, we have recently observed that in patients after HSCT, the TCR repertoire of T regs , as analyzed by spectratyping, is much more diverse as compared with the frequent oligoclonalities detected in conventional CD4 ϩ cells from the same patients (37).…”
Section: Subsequently Infused Hemopoietic Cells (R Laylor Et Al Pementioning
confidence: 58%
“…For example, Treg clones with higher avidity for minor histocompatibility alloantigens are more likely to preferentially expand and then undergo apoptosis under the conditions of immune reconstitution found in our patients. This process may further skew the diversity of the Treg TCR repertoire by selectively depleting those Tregs that are capable of suppressing alloimmune responses in vivo (60,61). Second, previous studies have shown that the expression of tissue homing receptors on Treg changes during the conversion from naive to activated/memory phenotype (62).…”
Section: Discussionmentioning
confidence: 99%